2012
DOI: 10.1016/j.jtcvs.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Combined proximal stent grafting plus distal bare metal stenting for management of aortic dissection: Superior to standard endovascular repair?

Abstract: Combined proximal descending aortic endografting plus distal bare metal stenting for aortic dissection provides favorable short-term outcomes and decreases late distal aortic complications compared with conventional endovascular repair. These results support a more widespread application of this approach. A prospective, randomized trial is needed before definite conclusions can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Results similar to these have led investigators to suggest that further false lumen thrombosis may be promoted by extending stent coverage across the entire descending thoracic aorta. Hofferbeth et al 22 compared this technique with a cohort of patients treated with coverage of the proximal entry tear alone and found that patients with more descending thoracic aorta coverage were more likely to have complete false lumen thrombosis in the thoracic aorta (72% vs 46%) and abdominal aorta (40% vs 15%).…”
Section: Discussionmentioning
confidence: 99%
“…Results similar to these have led investigators to suggest that further false lumen thrombosis may be promoted by extending stent coverage across the entire descending thoracic aorta. Hofferbeth et al 22 compared this technique with a cohort of patients treated with coverage of the proximal entry tear alone and found that patients with more descending thoracic aorta coverage were more likely to have complete false lumen thrombosis in the thoracic aorta (72% vs 46%) and abdominal aorta (40% vs 15%).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 We would consider using bare stents to prevent rupture induced by the proximal stent-graft only when the true lumen is compressed extensively, as others have recommended. 18,19 Although successful treatment of the distal tear at the CA by the combined use of a bare stent and coils has been reported, 20 we still worry about the dislocation of coils and also the effectiveness against large intimal tears. Thus, we think its application is limited.…”
Section: Discussionmentioning
confidence: 99%
“…This strategy is in alignment with a recently presented technique including combined proximal stent grafting plus distal bare metal stenting for management of aortic dissection. 7 Using the Evita prosthesis while inserting the distal stent endograft via the frozen elephant trunk, we aimed for definitive one-staged surgery. From a technical point, we discovered that only custom-made insertion knobs of the Evita device are appropriate to use, since otherwise the frozen elephant trunk part of the prosthesis may be difficult to apply distally to the descending aorta.…”
Section: Discussionmentioning
confidence: 99%